An Innovative Technique for Static Post-Operative Splintage - Neeta Kulkarni Patel; Parag Sahasrabudhe (Indian Journal of Plastic Surgery)
Dental Impression Compound was found to be a useful material to fabricate immediate postoperative and maintenance splints after contracture release in 50 cases.